Total column ozone content and aerosol optical thickness measurements: instrument performance analysis - Aculinin, Alexandr (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2006)

(untitled)
Measurements of total ozone content (TOC) and aerosol optical thickness (AOT) at